2022
DOI: 10.1590/1516-4446-2021-2026
|View full text |Cite
|
Sign up to set email alerts
|

Web-based exercise interventions for patients with depressive and anxiety disorders: a systematic review of randomized controlled trials

Abstract: Objective: The number of people suffering from depression and/or anxiety has increased steadily due to the coronavirus disease 2019 (COVID-19) pandemic. In this context, web-based exercise interventions have emerged as a potential treatment strategy. The objective of this study was to synthetize evidence from randomized controlled trials regarding the effects of web-based exercise interventions on patients with depressive and/or anxiety disorders. Methods: Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…This is in line with MDD exercise guidelines that recommend exercising within a range of 50 to 85% of maximum HR [17]. Alternative training options could be provided via an application when the regular training is difficult to perform for patients [15].…”
Section: Exercise Prescriptionsupporting
confidence: 69%
See 3 more Smart Citations
“…This is in line with MDD exercise guidelines that recommend exercising within a range of 50 to 85% of maximum HR [17]. Alternative training options could be provided via an application when the regular training is difficult to perform for patients [15].…”
Section: Exercise Prescriptionsupporting
confidence: 69%
“…To date, few studies have addressed the reduction of depressive symptoms through web-based exercise. In a recent review, only three studies were included [15]. Two studies could not demonstrate an improvement of depressive symptoms compared to the control condition [19, 27], while one study demonstrated a favorable effect of web-based yoga [28].…”
Section: Web-based Exercise – Attitudes Challenges and Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…Other systematic reviews have focused on the effects of exercise on depressive mood-related symptoms [ 24 , 39 , 40 , 41 , 42 ], although to date, only two previous reviews and meta-analyses have assessed the impact of physical exercise on cognitive symptoms in adults with depression [ 22 , 43 ], including global cognition and different cognitive domains as outcome measures (e.g., processing speed, attention/vigilance, verbal learning and memory, and visual learning and memory). Supplement The cognitive domains selected in both studies were categorized according to the structure of the MATRICS Consensus Cognitive Battery (MCCB) [ 44 ].…”
Section: Introductionmentioning
confidence: 99%